Draft Annual Plan, 2003-04 Volume II Statement I To XVI ( Except VIII To XI) Excluding Statement III Which is in Supplement of Volume II - Planning Commission (Planning Commission, 2003)
Summary statement of major headwise-outlays and expenditure, A Prime Minister Gramodaya Yojna-outlays and expenditure, Prime Minister Gramodaya Yojna-physical targets and achievements, centrally sponsored schemes-outlays and expenditure, District Plan-outlays and expenditure.
Government of Uttar Pradesh, State Planning Commission